Image-guided Cryotherapy for Musculoskeletal Tumors - Scandiffio, Rossella; Bozzi, Elena; Ezeldin, Mohamed; Capanna, Rodolfo; Ceccoli, Matteo; Colangeli, Simone; Donati, Davide M.; Colangeli, Marco (Current Medical Imaging, 2021)
Background: This article represents a review of the use of image-guided cryotherapy in the treatment of musculoskeletal tumor lesions. Cryotherapy is able to induce a lethal effect on cancer cells through direct and indirect mechanisms. In this manuscript, we combined our experience with that of other authors who have published on this topic in order to provide indications on when to use cryotherapy in musculoskeletal oncology. Discussion: Image-Guided percutaneous cryotherapy is a therapeutic method now widely accepted in the treatment of patients with musculoskeletal tumors. It can be used both for palliative treatments of metastatic bone lesions and for the curative treatment of benign bone tumors, such as osteoid osteoma or osteoblastoma. In the treatment of bone metastases, cryotherapy plays a major role in alleviating or resolving disease-related pain, but it has also been demonstrated that it can have a role in local disease control. In recent years, the use of cryotherapy has also expanded for the treatment of both benign and malignant soft tissue tumors. Conclusion: Percutaneous cryotherapy can be considered a safe and effective technique in the treatment of benign and malignant musculoskeletal tumors. Cryotherapy can be considered the first option in benign tumor lesions, such as osteoid osteoma, and a valid alternative to radiofrequency ablation. In the treatment of painful bone metastases, it must be considered secondarily to other standard treatments (radiotherapy, bisphosphonate therapy, and chemotherapy) when they are no longer effective in controlling the disease or when they cannot be repeated (for example, radiotherapy).
Keywords: palliative care